Kepemimpinan Prophetik: Penelitian - Imam Purnomo; Joko Mujianto; Khabib Abdullah; Setyo Pamungkas; Siswadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This research explores the concept and implementation of prophetic leadership within the context of educational management as a paradigm that integrates spiritual and moral values. Prophetic leadership is defined as a model that prioritizes a clear vision, the ability to inspire, and a commitment to individual character development. This article aims to analyze implementation strategies, the challenges encountered, and the significant impact of this leadership model on educational institutions. Through a literature review, it was found that key strategies involve developing value-based visions and missions, participatory decision-making, and strengthening character education through the values of discipline, patience, and perseverance. The findings indicate that prophetic leadership, which also adopts transformational elements, is capable of creating a positive school climate, increasing teacher and student motivation, and fostering a sustainable culture of innovation. Nevertheless, its implementation faces tangible challenges such as rigid organizational cultures, resistance to change, and limited resources. This study concludes that prophetic leadership is a crucial holistic approach to improving educational quality and shaping future generations with moral integrity and high academic competence. Educational managers are encouraged to adopt these values through continuous training and systemic evaluation to achieve more comprehensive educational goals.